Outcome of aneurysmal subarachnoid hemorrhage using Ogilvy and Carter grading system after clipping - Jha, Prabhat; Jha, Binit Kumar; Khambu, Bikesh; Shrestha, Rajendra; Jha, Rajiv; Bista, Prakash (Nepal Journal of Neuroscience, 2022)
Aneurysmal subarachnoid hemorrhage is a major cause of death and disability. Scales that have been used to prognosticate patients with subarachnoid hemorrhage are Hunt and Hess scale, World Federation of Neurosurgical Societies scale, Fischer grading system. But these scales aren’t inclusive enough to account for all factors related with prognosis of the disease. So Ogilvy and Carter scale has been developed to account for all of these factors. This study has been done to evaluate the effectiveness of Ogilvy and Carter Score in prognosticating patients with aneurysmal subarachnoid hemorrhage. This is a prospective analytical study conducted at National Academy of Medical Sciences, National Neurosurgical Referral Center, Bir Hospital, Kathmandu, Nepal. Fifty patients with aneurysmal subarachnoid hemorrhage were included. Hunt and Hess score 1-3 is independently associated with favourable GOS. (p value- 0.000013). Aneurysm size less than or equal to 10 mm is independently associated with favourable GOS. (p value-0.003575). Similarly age less than 50 years was independently associated with favourable GOS. (p value- 0.01354). The incidence of vasospasm, hydrocephalus, electrolyte imbalance, myocardial infaraction and pulmonary edema were higher in patients with Hunt and Hess score > 2, aneurysm size > 10 mm, age >50 years and Fischer score >2. Higher Ogilvy and carter score was associated with unfavourable GOS at 6 months (p value- 0.002). In conclusion Ogilvy and Carter scale can serve as a useful for prognosticating patients with aneurysmal subarachnoid hemorrhage.